Kebebasan Pers dalam Konteks KUHP Pidana: Menyoal Undang-Undang sebagai Fungsi Komunikasi - Rahayu, Mella Ismelina Farma (FIkom Unisba, 2007)
In his book, The Limits of Law, Anthony Allots stated that regulation is no more that a communication system based on Wittgenstein’s phrase: the language game. Regulations always ask the same questions: who’s the actor of communication? For whom the regulations been imposed? How did its communication method? What were communication obstacles which disturbed the communication process? Speaking about press regulations, which cutting-off and narrowing the freedom of press in Indonesia as imposed by KUH Pidana, it was clear enough that such regulation’s function mainly part of repressive acts, not preventive purposes.